Voting right rotation, behavior of committee members and financial market reactions: Vidence from the U.S. Federal Open Market Committee - Michael Ehrmann; Robin Tietz; Bauke Visser (European Central Bank (ECB), 2021)
Whether Federal Reserve Bank presidents have the right to vote on the U.S. monetary policy committee depends on a mechanical, yearly rotation scheme. Rotation is without exclusion: also nonvoting presidents attend and participate in the meetings of the committee. Does voting status change behavior? We find that the data go against the hypothesis that without the voting right, presidents use their public speeches and their meeting interventions to compensate for the loss of formal influence; rather, they support the hypothesis that the voting right makes presidents more involved. We also find that speeches move financial markets less in years that presidents vote. We argue that these discounts are consistent with their communication behavior.
Keywords: D71; D72; E58; 330; voting right rotation; monetary policy committee; central bank communication; FOMC; financial market response